Efforts to Boost Students' Self-Confidence Through Group Counseling Services in Junior High Schools - Ummi Kalsum Lubis (Universitas Negeri Medan, 2025)
Most students at SMP Negeri 5 Percut Sei Tuan exhibit low self-esteem traits such as fear, shyness, cheating, and anxiety. These traits affect students' emotional well-being and make them less enthusiastic about attending classes. The purpose of this study is to improve students' self-confidence through group counseling services in junior high schools. The research methodology employed Guidance and Counseling Action (GCA), implemented in two cycles. Each cycle consists of four phases: planning, implementation, observation, and reflection. The research subjects were eighth-grade students with low self-confidence. The research findings showed that after receiving group counseling services, students' self-confidence improved. At school, group counseling services have proven to be a successful alternative solution for enhancing the self-confidence of junior high school students.